A magnetically recyclable iron oxide-supported copper oxide nanocatalyst (Fe3O4–CuO) for one-pot synthesis of S-aryl dithiocarbamates under solvent-free conditions. Issue 38 (30th March 2016) - Aryanasab, F.
Abstract : A convenient preparation of S -aryl dithiocarbamates from amine, carbon disulfide and aryl iodide was developed by using the Fe3 O4 –CuO nanocatalyst under solvent free conditions. Abstract : A green, convenient and efficient procedure is reported for the synthesis of S -aryl dithiocarbamates by a simple one-pot three component Ullmann-type condensation of an amine, carbon disulfide and an aryl iodide. Magnetically separable and reusable copper oxide (Fe3 O4 –CuO) nanoparticles are used as a heterogeneous catalyst under base- and solvent-free conditions. Nanoparticles with an average size of 10–20 nm has been successfully prepared by a simple precipitation method in aqueous medium from readily available inexpensive starting materials. The catalyst could be easily separated from the reaction mixture by using an external magnet and recycled four times without significant loss in its activity.